Kategori Fatis Bahasa Minangkabau dalam Kaba Rancak di Labuah - Yusra, Hasnawatil; Agustina, Agustina; Tamsin, Andria Catri (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The working paper to describe fatis Minangkabaunes language in Kaba â€œRancak diLabuahâ€ from side of its shape and function. The collection of the data done through two main techniques, that is tapping and writing techniques. Tapping technique is known as a basic technique in scrutnizing method, this technique is used to tap the language using in writing method not with the people are talking, while the writing technique is used to write the data related to the shape and fatis function. Analization of the data done by organize and put the data in the right order based on work hippotesa.based on the result of the research, the researcher conludes that first, from the shape, fatis canbedevided 3 offatis particles, 8 of fatis fusions, 6 of fatis words, and 18offatis phrases. Second, from the function of fatis, ithas 5 function thatis, explains, strengthens, convices and start the story/ new paragraph.